Fragilités matérielles - Jérôme Denis; David Pontille (Revue d'anthropologie des connaissances)
This introductory article shows how the prism of fragility can be used as a way to conceptually and empirically further the research work that has foregrounded the material part of human societies by focusing on the agency of artifacts and the strength of matter. It discusses the richness and limits of fragility as a notion, starting with its conception in materials science which is notably based on the idea of external constraint. It then demonstrates, drawing on the articles of the special issue, that another conception of material fragility is possible, which opens up the way to an investigation of the sociomaterial interdependencies that contribute to holding things together. Because it does not pin down things to the sole concern for shock and loss, material fragilities can be conceived, and practiced, as generative.